2022
DOI: 10.1155/2022/5501171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small Nucleolar RNA SNORD60 as a Potential Biomarker and Its Clinical Significance in Lung Adenocarcinoma

Abstract: Non-small-cell lung cancer (NSCLC) is the leading cause of cancer deaths in the world and often diagnosed at an advanced stage, so it is urgent to explore the pathogenesis and new diagnostic biomarkers. Accumulated evidences suggested that small nucleolar RNAs (snoRNAs) played a key role in the development and progression of NSCLC. To examine differential expression snoRNA profile and identify snoRNAs with clinical significance in lung adenocarcinoma (LUAD), The Cancer Genome Atlas (TCGA) LUAD RNA sequencing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Here, our study based on GNG7 is similar to, but more distinctive from, the newly identified biomarkers for LUAD in the latest literatures. In our study, we demonstrated GNG7 as an independent prognostic risk factor in LUAD (Supplementary Table S4) (Wan et al, 2021;Tian W. et al, 2022;Zhang et al, 2022;Zhou et al, 2022). Moreover, we constructed a nomogram combined with other clinical independent prognostic risk factors to predict the prognosis of LUAD patients reliably.…”
Section: Discussionmentioning
confidence: 53%
“…Here, our study based on GNG7 is similar to, but more distinctive from, the newly identified biomarkers for LUAD in the latest literatures. In our study, we demonstrated GNG7 as an independent prognostic risk factor in LUAD (Supplementary Table S4) (Wan et al, 2021;Tian W. et al, 2022;Zhang et al, 2022;Zhou et al, 2022). Moreover, we constructed a nomogram combined with other clinical independent prognostic risk factors to predict the prognosis of LUAD patients reliably.…”
Section: Discussionmentioning
confidence: 53%
“…We also excluded 79 basic studies and 26 reviews from the remaining 105 eligible studies. Finally, we included a total of 49 studies in our qualitative synthesis, with 21 studies focused on diagnosis, 9 29 and 41 studies focused on prognosis. 11 , 13 15 , 17 , 18 , 20 , 22 , 24 , 25 , 27 , 28 , 30 56 Figure 1 provided detailing information about the selection process, which based on preferred reporting items for systematic reviews and meta-analyses (PRISMA) standards.…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression of SNORA42 and SNORA71A in lung cancer was found to be associated with poor prognosis 40 , 47 . Another study on lung cancer implicated SNORD60 in the causation of lung adenocarcinoma and highlighted its role as a marker of poor prognosis 48 . A study identified the prognostic value of HBII-239 snoRNA in T cell lymphoma, and its elevated level indicated a good prognosis 49 .…”
Section: Hotspots and Frontiersmentioning
confidence: 99%